Business opportunities in 5G mobile technology - Anna-Greta Nyström; Ilia Gugenishvili (International Telecommunications Society (ITS), 2019)
The question of how actors perceive business opportunities has puzzled both researchers and practitioners for decades. In the era of artificial intelligence, machine learning, and the Internet of things, many actors of the technology-intensive industries question how to use new technology to create value, and how to monetize new service concepts. In this paper, we focus on the next mobile communications technology, 5G, as one of the potential value-creators for the future that holds business opportunities for its utilizers and deployers. The concept of business opportunities is strongly associated with research on entrepreneurship (cf. Carlsson et al., 2003). Entrepreneurial opportunities consist of a set of ideas, beliefs, and actions that enable the introduction of goods, services, raw materials, and organizing methods in the absence of current markets for them (Sarasvathy et al., 2003). The research stream of entrepreneurial opportunities (cf. Alvarez & Barney, 2007, 2010; Dimov, 2007, 2011; Eckhardt & Shane, 2003) can offer new insights into the development of opportunities in high technologyintensive fields, and especially as regards the development of 5G. Strategies for opportunity identification, exploitation, and value creation are vital in the 5G era, as non-ICT traditional business sectors begin to deploy wireless technologies (e.g., factories, automotive, etc.). Researchers expect that 5G will change the business models and business ecosystems; it will also better address the evolving needs of customers (cf. Kliks et al., 2018). Unlike already existing mobile communications systems, 5G allows integration of vertical industries, e.g., energy, media, health, factories, and the automotive industry (5G-PPP, 2016). Thus, specialized companies will be able to provide services and establish positions in the value chains and actor networks. This is a major transformation compared to an environment dominated by bilateral relationships between mobile operators and their customers...
Keywords: 330